Postgraduate Orthodontics Students' and Mentors' Perceptions of Portfolios and Discussion as Tools for Development of Reflection. Issue 9 (1st September 2016) - Tonni, Ingrid; Mora, Luca; Oliver, Richard G.
Abstract : The aim of this study was to analyze the effects of a portfolio learning strategy designed to develop students' reflection abilities in a postgraduate orthodontic program in the UK. Nine first‐year postgraduate orthodontic students and seven mentors participated in the one‐year program, which included a reflective portfolio, mentorship, and discussion. After the program, the students' and mentors' perceptions were collected using focus groups and individual interviews, respectively. The data were analyzed using thematic analysis. Four categories emerged. The first, reflection, was considered a skill to learn, and time was needed for students to fully understand its meaning and achieve its outcomes. The second theme, characteristics of reflection, was descriptive at the beginning and more critical at the end of the experience. The third theme, outcomes of reflection, involved students' improved problem‐solving and action‐planning abilities and increased self‐awareness, motivation, confidence, and communication skills. In the fourth theme, stimulation of reflection, students did not agree with mentors regarding the importance of reflective writing, but they recognized the value of the portfolio's reflective log in facilitating the reflective process. There was greater agreement between students and mentors regarding discussions with mentors and among peers as tools to achieve higher levels of reflection. Overall, these students and mentors considered the strategy an effective tool for improving students' reflection.